Controllable fabrication of single-crystalline, ultrafine and high-silica hierarchical ZSM-5 aggregates via solid-like state conversion. Issue 41 (12th May 2017) - Li, Hongyao; Wang, Yaquan; Meng, Fanjun; Gao, Fei; Sun, Chao; Fan, Chunyang; Wang, Xiao; Wang, Shuhai
Abstract : Single-crystalline, ultrafine and high-silica HA-ZSM-5 aggregates were directly synthesized via SSC method using HTAB as the mesoporogen through a S-1 seed-induced route. Abstract : A series of single-crystalline, superfine and high-silica (SiO2 /Al2 O3 > 100) hierarchical ZSM-5 aggregates (denoted as HA-ZSM-5) with a tuneable crystal morphology and size, and rich intercrystalline mesoporosity, were facilely fabricated within a short reaction time using the commercially available n -hexyltrimethylammonium bromide (HTAB) as a mesopore template by a solid-like state conversion (SSC) route; the crystallization of HA-ZSM-5 is induced within 36 h at a HTAB/SiO2 ratio of 0.05 with the assistance of 2% silicalite 1 (S-1) seeds. Key factors (such as SiO2 /Al2 O3 ratio, seed/SiO2 ratio and HTAB/SiO2 ratio) in controlling the crystal size and morphology have been systematically investigated. The formation process was studied by monitoring the morphology, relative crystallinity and structural properties of the samples at different crystallization times. The preparation of HA-ZSM-5 zeolites may be a kinetics-controlled dissolution/induction/growth/aggregation process and the possible formation mechanism was put forward based on experimental results. The obtained samples were characterized by several techniques and the representative HA-ZSM-5 (HA-167-2S-5H) was evaluated in a methanol to propylene (MTP) reaction. Compared with the blank sample (denoted as C-ZSM-5) without HTAB addition and a commercial ZSM-5 zeolite (denoted as C1 -ZSM-5), the HA-167-2S-5H sample exhibited the highest selectivity towards propylene (40.1% vs. 33.1% and 38.7%) and butylene (22.9% vs. 17.2% and 21.4%), and especially the longest catalytic lifetime (22 h vs. 6 h and 1.5 h). The remarkably enhanced catalytic performance of HA-167-2S-5H could be attributed to the synergistic effect of the excellent structural properties, appropriate acidity and good accessibility of acidic sites. In addition, the introduction of interparticle mesopores not only enhances the utilization of zeolite acid sites by the enlarged external surface but also partially suppresses side reactions and inhibits coke deposition by shortening the micropore diffusion path lengths, leading to an increased conversion.